Cancer Chemopreventive, Antiproliferative, and Superoxide Anion Scavenging Properties of Kluyveromyces marxianus and Saccharomyces cerevisiae var. boulardii Cell Wall Components. (2nd January 2018) - Fortin, Olivier; Aguilar-Uscanga, Blanca; Vu, Khanh Dang; Salmieri, Stephane; Lacroix, Monique
ABSTRACT: This study investigated the cancer chemopreventive, the antiradical, and the antiproliferative properties of polysaccharides extracts from cell wall of Saccharomyces boulardii and Kluyveromyces marxianus . β-glucan, mannan, and chitin were also quantified to identify the most important extract responsible for these biological properties. Soluble and insoluble glucans as well as mannoprotein were extracted from cell wall using single hot-alkaline method. Superoxide anion scavenging (antiradical capacity), NAD(P)H: quinone reductase (QR) (EC 1.6.99.2) induction, and antiproliferative assays were done for the evaluation of biological properties of those extracts. The insoluble glucan from S. boulardii revealed the most relevant biological properties by increasing QR activity and exhibiting the highest growth inhibition against colorectal cancer cells. Moreover, high amount of glucan, high glucan/total sugars ratios, and low chitin/glucan ratios were shown to have an impact on enhancing cancer chemopreventive and antiproliferative properties. To our knowledge, this is the first study that demonstrates QR activity by yeast cell wall components in a dose-dependent manner.